The influence of surrounding vegetation on the flora of post-mining area - Kopeć, Dominik; Zając, Izabela; Halladin-Dąbrowska, Anna (Biodiversity: Research and Conservation, 2012)
In 2007, extensive botanical studies were carried out in the Gagaty Sołtykowskie Reserve (Małopolska Upland, southern Poland) to compile comprehensive flora inventories n separately for a post-mining area and the surrounding forest. The main aim of the study was to assess the influence of the surrounding vegetation on the flora of a former ceramic clay mine located in the middle of a dense forest. The results show that over 30 years after closure, the former mine is now home to several valuable and protected species of vascular plants, with the rate and direction of succession determined mainly by the surrounding vegetation. Because ruderal species have no direct access to the area, non-synanthropic, indigenous species are dominant in the Gagaty Sołtykowskie Reserve (GS).